2020
DOI: 10.3324/haematol.2020.253047
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation: a global coagulation procedure to investigate hypo- and hyper-coagulability

Abstract: he article by van Paridon et al. 1 published in this issue of Haematologica on results of thrombin generation (TG) in cardiovascular disease and mortality, stemming from the Gutenberg Health Study, provides an opportunity to comment on TG as a global laboratory procedure to investigate hypo-and hyper-coagulability. TG as a laboratory test was developed in the early 1950s by McFarlane and Biggs 2 and was based on the activation of coagulation in whole blood or plasma by triggers such as tissue factor or cephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our model predictions were in good agreement with the reported experimental findings in the literature. Indeed, it was shown experimentally that elevated ETP and peak concentrations values were associated with hypercoagulable states [42], while an increased time to peak was associated with poor coagulation [43,44]. It was also shown that the lag time has a minimal effect on coagulation, which also agrees with our model findings.…”
Section: Discussionsupporting
confidence: 90%
“…Our model predictions were in good agreement with the reported experimental findings in the literature. Indeed, it was shown experimentally that elevated ETP and peak concentrations values were associated with hypercoagulable states [42], while an increased time to peak was associated with poor coagulation [43,44]. It was also shown that the lag time has a minimal effect on coagulation, which also agrees with our model findings.…”
Section: Discussionsupporting
confidence: 90%
“…Our results related to most thrombin generation parameters confirm this statement, except for the ETP performed using low tissue factor (TF), which emerged as an important tool to evaluate the bleeding potential of hemophilia A patients. The area under the curve, known as ETP, represents the net amount of thrombin generation, reflecting the balance between procoagulant and anticoagulant forces [19], being the parameter that most correlates with clinical findings. LBP patients showed a higher ETP value compared with those with BPH, which means a larger area under the curve, that is, less inhibition of the thrombin formed by the natural anticoagulation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A (nanomolar) and endogenous thrombin potential (nanomolar per minute) were recorded (Tripodi, 2020). Owing to the reduced amount of platelet-poor plasma available (because of the very high haematocrits), the thrombin generation assay was not performed in 2 of 15 (13%) EE− and 13 of 30 (43%) EE+, and not performed in 1 of 10 (10%) LL, owing to technical failure.…”
Section: Thrombin Generationmentioning
confidence: 99%